Seismic vulnerability: from building evaluation to a typology generalization - Lamego, P. (2012)
Outlining the best strategies for seismic risk mitigation requires that both benefits and costs of retrofitting are known in advance. The assessment of the vulnerability of building typologies is a first step of a more extensive effort, concerning the analysis of the viability of seismic risk mitigation and taking into account retrofitting costs. The methodology adopted to obtain the seismic vulnerability of some classes of residential buildings existing in mainland Portugal is presented. This methodology is based on a structural analysis of individual buildings belonging to the same typology. An application example is presented to illustrate the methodology. Fragility curves of “boxed” building typology are also presented and broken down into three height classes: low-rise, medium-rise and high-rise. These curves are based on average capacity spectra derived from several individual buildings belonging to the same typology.